Antifungal resistance and predominance of virulence determinants among Candida albicans isolated from various clinical specimens - Houdaii H. El-Houssaini; Walid Faisal Elkhatib; Omnia M. Elnabawy; Hebatallah A. Nasser (Ain Shams University, 2019)
Candida albicans remains the most common cause of hospital-acquired fungal infections due to its virulence determinants. Resistance to antifungal therapy has increased dramatically, narrowing the few available therapeutic options due to their potential toxicity. However, the association between C. albicans virulence determinants and resistance profiles needs further investigation. C. albicans (n= 25) isolated from various clinical samples were identified. Antibiogram analysis of the tested isolates against different antifungal agents was performed and their minimum inhibitory concentrations (MICs) were verified. Virulence determinants including extracellular hydrolytic enzymes, biofilm formation, and cell surface hydrophobicity (CSH) were investigated. Correlations between virulence determinants and resistance profiles of the experimented isolates, in addition to their potential association with the source of clinical specimens, were analyzed. All isolates were amphotericin B, nystatin and micafungin sensitive, while 100% were clotrimazole, fluconazole and voriconazole resistant. Extracellular hydrolytic activities were detected in 52, 68 and 100% of the tested isolates for phospholipase, protease, and hemolysin, respectively, while CSH and biofilm production was shown in 24 and 20% of isolates, respectively. CSH had significant (p < 0.05) positive as well as negative associations with amphotericin B and fluconazole MICs, respectively. Source of clinical isolates showed significant (p < 0.05) influence on some resistance and virulence patterns.